Factors affecting individual customers’ intention to use NFC mobile payment services in Ho Chi Minh City - Nga, Tran Kieu; Anh, Le Tu (Edelweiss Applied Science and Technology, 2025)
This study aims to identify the key factors influencing the intention to adopt mobile payments using NFC technology among individual users in Ho Chi Minh City. The research design includes two phases: qualitative and quantitative. The qualitative phase was conducted through expert consultation to refine the scales, ensuring their relevance and understandability. The quantitative phase used an online questionnaire, based on validated scales from previous studies, to survey 385 people aged 18 to 55 who were technologically savvy and familiar with digital financial services. Data analysis focused on six factors: trust, perceived ease of use, perceived usefulness, social influence, technology readiness, and service quality. The results showed that all of these factors had a positive and significant impact on the intention to use NFC technology, with trust and social influence being the two most influential factors. The study provides important practical implications for businesses, financial institutions, and policymakers in developing strategies to promote digital payments in Vietnam.